Educating the Catholic People : Religious Orders and Their Schools in Early Modern Italy (1500-1800). - Salomoni, David (Boston : BRILL, 2021)
In Educating the Catholic People, Salomoni offers a new perspective on the pedagogical, institutional, and political innovations introduced in Italy by religious teaching congregations between the sixteenth and eighteenth centuries.
3.3 Women, Nuns, Teachers: The 'Educandato' of Saint Charles -- Chapter 5 The End of an Educational Season: The Schools of Religious Orders between Scientific and Political Revolutions (17th-18th cc.) -- 1 The Scientific Culture: Religious Orders on the Eve of Modernity -- 1.1 Famiano Michelini and the Galilean Piarists -- 1.2 Baranzano Redento -- 2 School Reforms in the Age of Enlightenment -- 2.1 The European Situation -- 2.2 The Situation in Italy: The Italian States and the Religious Orders -- 3 Conclusion -- Bibliography -- Consulted Archives -- Published Sources -- Early Printed Books (before 1830) -- Modern Bibliography (after 1830) -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books